Village Tourism, A Case of the Commodification of Place and Conservation in Samiran Village, Central Java, Indonesia - Umar Baihaqki; Abdul Rahman; Rosita Adiani (Communications of International Proceedings, 2021)
Village tourism is a means of locally driven development. The concept emphasizes the commodification of cultural and environmental resources in the village for tourist consumptions. Tourism objects and their supporting facilities are managed by village residents. Such characteristics of a tourist village make this type of tourism an example of community-based tourism. The success of tourism in supporting the well-being of the locals is on par with the community's effectiveness in organizing themselves to run the tourism business. This article describes how tourism has become an alternative economy for the locals besides agriculture in Samiran village, Central Java, Indonesia. The practice of tourism brings a new meaning of local culture for the host. Young villagers start to practice traditional dances and perform in front of tourists. Local villagers renovate their properties into local homesteads for guests. However, the performative delivery of tourism experience raises several concerns regarding the authenticity of traditions.
Keywords: Village Tourism; Commodification; Authenticity